The influence of sustainable organization practices and employee well-being on turnover intention - Wong, Foong Yee; Jo, Ann Ho; Azahari, Aziany Riziana (Universiti Putra Malaysia Press, 2016)
The aim of this study is to determine (i) the level of implementation of sustainable organisation practices; (ii) the relationship between sustainable organisation practices and employee well-being; and (iii) the relationship between employee well-being and turnover intention. This study applies descriptive quantitative and bivariate methods. The sample of the study comprised 200 employees working in Government-Linked Companies. All instruments in this research were measured using a 5 point Likert scale. Based on Multiple Regression analysis, the results revealed that Job Control was the most dominant practice influencing Employees’ Well-Being. It showed that the more control over one’s work the more he or she were satisfied with their jobs. Employees’ Well-Being was seen to be negatively related to Turnover Intention. This study is a significant guide and reference for managers and future researchers in determining the best work practices for the organization in the long term.